Parental experiences using the Therapy Outcomes by You (TOBY) application to deliver early intervention to their child with autism. (19th May 2019) - Rogerson, Jessica; Falkmer, Marita; Cuomo, Belinda; Falkmer, Torbjorn; Whitehouse, Andrew J. O; Granich, Joanna; Vaz, Sharmila
ABSTRACT: Purpose : As computer-based interventions become commonplace for parents of children with neurodevelopmental disorders, this study sought to understand the experience of using a parent-delivered supplementary early intervention therapy for children with autism spectrum disorder grounded in a variety of behavioral, sensory, developmental, and relationship-based approaches and delivered via a tablet device. Methods : Parental experiences using the 'Therapy Outcomes by You' (TOBY) application were collected through semi-structured interviews with 17 parents. Results : Parents reported TOBY facilitated parent–child engagement, provided ideas for therapeutic activities, created feelings of empowerment, and positively impacted their child's development. Barriers to use included preparation time, execution of the intervention, and individual strengths and weaknesses of their child. Conclusion : The overall parental experience of TOBY was positive when use of the application aligned with parental proficiency, opportunities for use, and importantly, the needs of the child.